2022
DOI: 10.3390/ijms23095082
|View full text |Cite
|
Sign up to set email alerts
|

Complex N-Linked Glycosylation: A Potential Modifier of Niemann–Pick Disease, Type C1 Pathology

Abstract: Complex asparagine-linked glycosylation plays key roles in cellular functions, including cellular signaling, protein stability, and immune response. Previously, we characterized the appearance of a complex asparagine-linked glycosylated form of lysosome-associated membrane protein 1 (LAMP1) in the cerebellum of Npc1−/− mice. This LAMP1 form was found on activated microglia, and its appearance correlated both spatially and temporally with cerebellar Purkinje neuron loss. To test the importance of complex aspara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…LAMP-1 is expressed in the lysosomal membrane to modulate lysosomal activity. Deficiencies in NPC1 not only increased LAMP-1 expression but also LAMP-1 glycosylation [55]. Glycosylation is an essential process for lysosomal membrane proteins for vesicle trafficking, and the abnormal glycosylation of LAMP-1 possesses the potential to induce NPDC [56].…”
Section: Lysosomal Appearance and The Changes In Lysosomes In Npdcmentioning
confidence: 98%
See 1 more Smart Citation
“…LAMP-1 is expressed in the lysosomal membrane to modulate lysosomal activity. Deficiencies in NPC1 not only increased LAMP-1 expression but also LAMP-1 glycosylation [55]. Glycosylation is an essential process for lysosomal membrane proteins for vesicle trafficking, and the abnormal glycosylation of LAMP-1 possesses the potential to induce NPDC [56].…”
Section: Lysosomal Appearance and The Changes In Lysosomes In Npdcmentioning
confidence: 98%
“…Glycosylation is an essential process for lysosomal membrane proteins for vesicle trafficking, and the abnormal glycosylation of LAMP-1 possesses the potential to induce NPDC [56]. LAMP-1 hyper-glycosylation was observed in the cerebellum of NPC1 knock-out mice [55]. In addition, lysosomal membrane stabilization is associated with ion transportation through the lysosomal membranes.…”
Section: Lysosomal Appearance and The Changes In Lysosomes In Npdcmentioning
confidence: 99%
“…Such accumulation of sphingosine in NPC may be due to the observed reduction in sphingosine kinase 1 (SphK1), which is one of the enzymes that phosphorylates sphingosine [87]. In addition, alterations in lysosome-associated membrane protein 1 (LAMP1), a protein with highly glycosylated luminal domains that contributes to the integrity of the lysosomal membrane and glycocalyx, have also been found in NPC [88,89]. In the cerebellum of Npc1 −/− mice, differences in LAMP1 glycosylation have been observed that are associated with disease progression and the death of Purkinje neurons [89].…”
Section: Alterations In Lysosomal Glycocalyxmentioning
confidence: 99%
“…In addition, alterations in lysosome-associated membrane protein 1 (LAMP1), a protein with highly glycosylated luminal domains that contributes to the integrity of the lysosomal membrane and glycocalyx, have also been found in NPC [88,89]. In the cerebellum of Npc1 −/− mice, differences in LAMP1 glycosylation have been observed that are associated with disease progression and the death of Purkinje neurons [89]. Changes in LAMP1 glycosylation patterns have also been observed in studies with NPC1−/− cells, as they had high levels of mannose and sialylates, which can lead to changes in the lysosomal glycocalyx [35].…”
Section: Alterations In Lysosomal Glycocalyxmentioning
confidence: 99%